UPAYA PENINGKATAN CAPAIAN KINERJA FISIK PEMERINTAH KABUPAEN MAGELANG TAHUN 2020 - Wahyudi, Joko; Widiastuti, Nur (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
This research was carried out in the Development Administration Section of the Regional Secretariat of Magelang Regency by taking the object of the physical realization of the Magelang Regency Government which was supervised by 60 Regional Apparatus and Sections. This study aims to determine the physical achievements of the Magelang Regency Government that have not been optimal and find solutions to solve them. This study uses a qualitative descriptive method with the analyzed data consisting of primary data in the form of answers to observations and interviews and secondary data in the form of the Strategic Plan for Development Administration of the Regional Secretariat of Magelang Regency. The results of this study can be seen the causes of the non-optimal physical achievements of the Magelang Regency Government in 2020th, namely human resources in making a planning system for activities and inadequate infrastructure, changes in regulations, and external factors from the Regional Apparatus Work Unit such as failed auctions. To improve the physical achievements of the Magelang Regency Government in 2020th, it is necessary to increase the capacity of human resources, improve facilities and infrastructure, make policies that support the process of accelerating activities, supervise SKPD with low physical performance, and SKPD to carry out internal control and routine coordination. with related parties